Teacher's Challenges in Teaching English to Young Learner using Montessori Method - Chong Kai Jian; Widi Syahtia Pane (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2020)
Montessori Method is rarely used in Indonesia, especially Samarinda, and schools that apply this method are still relatively few. Teachers who choose this method and teach in schools that use this method are ready to face the challenges based on Pertiwi et al. (2020) when teaching children to learn English using a specific Method. This article reports a qualitative study that figures out the Teacher's challenges in teaching English for young learners around 5-6 years old using Montessori Method to